2008
DOI: 10.1007/s00125-008-1196-4
|View full text |Cite
|
Sign up to set email alerts
|

Type 2 diabetes-associated genetic variants discovered in the recent genome-wide association studies are related to gestational diabetes mellitus in the Korean population

Abstract: Aims/hypothesis New genetic variants associated with susceptibility to type 2 diabetes mellitus have been discovered in recent genome-wide association (GWA) studies. The aim of the present study was to examine the association between these diabetogenic variants and gestational diabetes mellitus (GDM). Methods The study included 869 Korean women with GDM and 345 female and 287 male Korean non-diabetic controls. We genotyped the single nucleotide polymorphisms (SNPs) rs7756992 and rs7754840 in CDKAL1; rs564398, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

22
188
3
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 219 publications
(216 citation statements)
references
References 50 publications
22
188
3
1
Order By: Relevance
“…Numerous genes related to fatty acid transport and metabolism require regulation of the PPARγ gene at the transcriptional level. PPARγ gene polymorphisms are reportedly relevant to the components of MS; however, other studies have shown different results (Hu et al, 2004;Chen et al, 2006;Jaziri et al, 2006;Gaulton et al, 2008;Cho et al, 2009;Gallicchio et al, 2009;Matsuo et al, 2009;Bego et al, 2011). Understanding the relationship of the high incidence of MS and PPARγ gene polymorphisms is important for determining the mechanism of MS occurrence and development as well as for identifying molecular markers that could be used for early diagnosis and prognosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous genes related to fatty acid transport and metabolism require regulation of the PPARγ gene at the transcriptional level. PPARγ gene polymorphisms are reportedly relevant to the components of MS; however, other studies have shown different results (Hu et al, 2004;Chen et al, 2006;Jaziri et al, 2006;Gaulton et al, 2008;Cho et al, 2009;Gallicchio et al, 2009;Matsuo et al, 2009;Bego et al, 2011). Understanding the relationship of the high incidence of MS and PPARγ gene polymorphisms is important for determining the mechanism of MS occurrence and development as well as for identifying molecular markers that could be used for early diagnosis and prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…PPARγ genetic polymorphisms include rs3856806, rs12490265, rs1797912, and rs1175543, which may be associated with MS. Differences exist among ethnicities and regions with respect to PPARγ gene polymorphisms; however, the results of various studies are not consistent regarding the extent in or causes of these differences (Hu et al, 2004;Chen et al, 2006;Jaziri et al, 2006;Gaulton et al, 2008;Cho et al, 2009;Gallicchio et al, 2009;Matsuo et al, 2009;Bego et al, 2011). Because the geographical and ethnic characteristics of members of the Xinjiang population can be used to reveal the cause of MS and thus provide a theoretical basis for its underlying genetic mechanism, this study examined the relationship of the PPARγ rs3856806, rs12490265, rs1797912, and rs1175543 polymorphisms, their haplotypes, and linkage disequilibrium with MS in Kazakh subjects in Xinxiang.…”
Section: Introductionmentioning
confidence: 99%
“…11,24 Additionally, several studies reported that the KCNQ1 gene was related to diabetes in the Korean population. [19][20][21] Most of these studies used a case subject-control subject design that tended to overestimate the risk of an SNP because case subjects and control subjects usually represented two extremes of the distribution of glucose tolerance. Therefore, we investigated whether the SNPs may indeed increase the risk of future T2DM in non-diabetic subjects.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, several reports showed that the common genetic variants analyzed in our study were significantly associated with diabetes in the Korean population. [19][20][21] Previous studies suggested that common variants in CDKAL1, SCL3A08, TCF7L2 and PPARG were also significantly associated with increased risk of future diabetes. 12,27 These discrepancies may be explained by the differences in the frequency and loci of genetic variants, ethnicity, population characteristics and follow-up durations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation